Analisa Determinaan Pemanfaatan Pos Pembinaan Terpadu (Posbindu) Penyakit Tidak Menular (Ptm) terhadap Penurunan Hipertensi di Gampong Lam Geu Eu Kecamatan Peukan Bada Kabupaten Aceh Besar - Misra Aulisa; Yadi Putra; Mansuriza Mansuriza (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
One type of prevention and promotion initiative, the Integrated Development Post (Posbindu) for PTM involves the community in early identification and routine monitoring of NCD risk factors, including hypertension. However, Posbindu services are still not widely used, even in Gampong Lam Geu Eu, the Peukan Bada working area. On May 16, 2026, this study was conducted. The purpose of this study was to examine the factors influencing the use of Posbindu PTM in reducing blood pressure. This study used a quantitative cross-sectional design. Using a complete sampling technique, the study population consisted of 64 hypertension patients who visited Posbindu PTM in Gampong Lam Geu Eu. A questionnaire with questions about knowledge, attitudes, family support, and availability of facilities was used to collect data. The chi-square test was used for univariate and bivariate data analysis. The majority of respondents had good knowledge (82.8%), good attitudes (81.3%), and good use of Posbindu (78.1%), according to the data. The use of Posbindu PTM was significantly correlated with knowledge, attitudes, family support, and facility accessibility (p < 0.05).Conclusion: Knowledge, attitude, family support, and facility availability are significant determinant factors in improving the utilization of Posbindu PTM. High community participation in Posbindu activities can help reduce the prevalence of hypertension.Recommendation: Efforts are needed to increase health education for the community through continuous counseling, strengthening family involvement in supporting hypertension patients, and providing complete and accessible health service facilities to improve the effectiveness of the Posbindu PTM program.